Forage potential of guaje (Leucaena leucocephala) at different densities plants and age of growth - Rojas-García, Adelaido Rafael; Maldonado-Peralta, María de los Ángeles; Hernández-Guzmán, Filogonio Jesús; Cruz-Hernández, Aldenamar; Chay-Canul, Alfonso Juventino; Ventura-Rios, Joel (Ecosistemas y Recursos Agropecuarios, 2021)
Due to the high costs of concentrated foods, it is necessary to promote the use of food sources that are economical and of high nutritional value, which help maximize animal production. The objective of this research was to evaluate the productive behavior of different densities of Leucaena leucocephala (guaje) in dry tropical climate. The study was carried out in the rainy season that covers from June to October 2017 in the experimental plots of the Facultad de Medicina Veterinaria No. 2 of the Universidad Autónoma de Guerrero, located in Cuajinicuilapa, Guerrero, Mexico. Leucaena was transplanted at a distance of 10 cm between plants and between rows of 1.5, 2 and 3 m, comprising the densities of 67, 50 and 33 thousand ha-1 plants, respectively. 30 days before the start of the investigation, a homogenization pruning was performed at a height of 1 m and subsequently six cutting stages were performed every 15 days (30, 45, 60, 75, 90 and 105 days). The highest dry matter yield was obtained in the 105 day interval with 7,627 kg DM ha-1and a density of 50,000 plants ha-1(p ≤ 0.05). The best planting density of Leucaena is when it has 50,000 ha-1plants, since it has the best structural characteristics and at a frequency of 90 days since it is when it reaches 95% of intercepted radiation.